Analisis Implementasi Metode Role Playing dalam Pembelajaran Kosa Kata Bahasa Jawa Kelas 2 SD Negeri 2 Tahunan: Analysis of the Implementation of the Role Playing Method in Learning Javanese Vocabulary for Grade 2 of 2-Year Elementary Schools - Rahmi, Vadia; Mufid (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Javanese language learning in elementary schools plays an important role in preserving regional culture and language. However, challenges in teaching Javanese vocabulary often arise, especially due to the dominance of Indonesian and foreign languages ??in everyday life. In SD Negeri 02 Tahunan, interactive learning methods are needed to increase students' interest in learning Javanese vocabulary. This study aims to analyze the implementation of the Role playing method in learning Javanese vocabulary in grade 2 of SD Negeri 02 Tahunan. The main objective is to identify obstacles and find solutions to improve the understanding of Javanese vocabulary for grade 2 students. This study uses a qualitative approach with a case study design. Data were collected through observation, interviews, and questionnaires from 25 grade 2 students. The implementation process of the Role playing method includes scenario preparation, drama implementation, and learning evaluation. The results showed that the majority of students gave a positive response to the Role playing method. The questionnaire data showed an average score of 948 out of a total of 1,250, with the highest score reaching 120. Students felt it was easier to understand vocabulary and were more confident in using Javanese after participating in Role playing activities. The role playing method has proven to be effective in improving students' understanding of Javanese vocabulary and active participation.